Foreign body aspiration presenting as a chronic lung disease: a unique finding in an elderly patient - Yasir Khan; Hamdan Mallick; Sobia Siddiqui; Mir Ibrahim Sajid; Saulat Hasnain Fatimi (Journal of the Pakistan Medical Association, 2023)
Foreign body aspiration is a serious clinical manifestation in the elderly and has a significant potential to cause life-endangering harm. In this unique report, we highlight the case of a seventy year old conscious male, who reported with complaints of chronic cough initially diagnosed as chronic bronchitis; however, on radiological examination, the infectious nidus was identified as a 5 cm long metallic nail in the right lower lung. Keywords: Chronic Cough; Geriatrics; Foreign Body; Aspiration; Thoracic Surgery.